ANALISIS EFISIENSI TURBIN UAP UNIT 1 DI PT. PJB UBJOM PLTU PULANG PISAU KALIMANTAN TENGAH - saputro, edi (Universitas Lambung Mangkurat, 2021)
This study aims to determine the performance of steam turbine PT. PJB UBJOM PLTU Pulang Pisau Kalimantan Tengah the results of data obtained during each performance test in commisioning 2016 and 2018. This research data is taken from the control room of PT. PJB UBJOM PLTU Pulang Pisau, variable data obtained in the form of load, main inlet steam temperature, main inlet steam pressure, HP heater feed outlet temperature, HP heater feed outlet pressure, main steam flow, and turbine by pass flow. The data is processed to get the turbine heat rate and the efficiency per time of each performance test and then averaging the data results over time, then comparing the turbine heat rate and the average efficiency of each performance test. The calculation of turbine heat rate using heat & mass balance method, turbine efficiency is obtained by comparing the energy of 1 kW with turbine heat rate and multiplying 100%. The result of the average heat turbine calculation per performance test highest ie September 2016 is 3,51and Juli 2018 is 3,27. The average value of turbine efficiency in September 2016 was 29,03% and Juli 2018 was 33,84. Turbine power plant performance of PT. PJB UBJOM PLTU Pulang Pisau increase from 2016 to 2018 by 4,81 %.Keywords:Turbin Heat Rate, Efisiensi Turbin